Implementation Based Education (Learning-Gradual) through Traditional Games Mambe Tampun - Feri Wagiono; Syahrial Shaddiq; Sakman Sakman; Suprayitno Suprayitno (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This article aimed to determine the application of learning-gradual based education through traditional games as a learning medium and to find out the strengths and weaknesses of implementing traditional games. This type of research is qualitative. The research subjects consisted of school principals, teachers, and students at MTS Miftahul Huda 2 Palangka Raya. Data collection techniques in this study used interview, observation, and documentation. The concept of education learning-gradual (LEGAL) combines the concept of learning gradually through traditional games as a medium of primary school learning in Miftahul Huda 2 Palangka Raya. In a traditional game, it has cultural worth and national character consists of mutual cooperation, cooperation, hard work, and democracy and can improve other aspects of child advancing, namely motoric, cognitive, emotional, language, social, spiritual, ecological as well as worth and moral aspects. The weakness is teachers struggle to divide the playgroup because students storm and run. It is hoped that teachers can implement traditional games as a learning medium, so that a nation's generation that loves local wisdom, culture, and morality is a relationship. Keywords: Education of Learning-Gradual, Traditional Games, .Mambe Tampun